Quality of life : perception from the public housing community in Melaka - Muhammad Faid Mohd Zamin (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2019)
Quality of life (QOL) is a very delicate and diverse subject matter and have garnered the attention of the masses for centuries. Each individual strives for perfect and harmonious well-being, sometimes interpreted as the QOL, although the accurate factors contributing towards it are elusive in nature. Till this day, QOL has been interpreted by many, but in spite of that, it has never been as diverse as it has since its inception. Different people with varying cultures and aspirations interpreted it according to their beliefs and norms, and sometimes what accounts as a good QOL may differ from others. In this research, a study is conducted to analyze the QOL of the low-income group in Melaka, according to their personal perception and views. As there are no data on wealth available, the low-income group of the population is substituted with the communities living in public houses. The instrument used is derived from the WHOQOL-BREF, which contains 22 social indicators that are assumed to affect an individual's QOL. A total number of 400 surveys were distributed fairly according to the three districts in Melaka and were focused on the public housing community entirely. The methods of analysis adopted in the study include descriptive statistics, Spearman's Rank Correlation Coefficient, cross-tabulation, and Partial Least Squares – Structural Equation Modelling (PLS-SEM). Overall, the response obtained from the respondents showed positive feedback, where a majority of them stated that they are experiencing a good QOL. Out of all the domains of QOL, it is identified that the 'environment', which encompasses the aspects of safety and security, home environment, financial resources, health and social care, leisure time, physical environment, and transport is the major contributing factor towards the overall QOL. The study also shows that there are no staggering differences between the B40 income threshold group of the population with the M40 group when it comes to their overall satisfaction with their perceived QOL.